IS THERE A PATH TO LASTING RELIEF? A REVIEW OF PHARMACOLOGICAL TREATMENT FOR VULVODYNIA - Karolina Kasprzak; Małgorzata Kuczek; Aleksandra Wiśniewska; Stanisław Kasprzak; Zuzanna Rabczak; Julia Marek; Justyna Tasior (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Vulvodynia is defined as discomfort of the vulva that lasts for at least three months and is clinically considered an idiopathic pain syndrome, presenting both diagnostic and therapeutic challenges.While non-pharmacological interventions such as pelvic floor physical therapy and psychotherapy provide relief for some patients, many require pharmacological treatment for persistent discomfort. Despite the availability of various pharmaceutical options, standardized treatment protocols are lacking, and comparative efficacy data remain limited. This review examines current pharmacological approaches for vulvodynia and assesses their effectiveness in managing symptoms. Results: Following a rigorous selection process, 29 articles met the inclusion criteria. The available evidence supports the efficacy of oral medications, particularly amitriptyline as a first-line treatment, and topical lidocaine in managing vulvodynia. Furthermore, the integration of physiotherapy alongside pharmacological management appears to enhance patient outcomes. Botulinum toxin injections did not yield statistically significant improvement in the studies included in the review. Conclusions: Amitriptyline and topical lidocaine have demonstrated efficacy for vulvodynia, particularly when combined with physiotherapy. Future research should focus on investigating the long-term efficacy of combined therapies and exploring the underlying mechanisms of vulvodynia to develop targeted treatments.